Proline accumulation in leaves of Periploca sepium via both biosynthesis up-regulation and transport during recovery from severe drought. - Yuyan An; Meixiang Zhang; Guobin Liu; Ruilian Han; Zongsuo Liang (PLoS ONE, 2013)
Drought resistance and recovery ability are two important requisites for plant adaptation to drought environments. Proline (Pro) metabolism has been a major concern in plant drought tolerance. However, roles of Pro metabolism in plant recovery ability from severe drought stress are largely unexplored. Periploca sepium Bunge has gained increasing attention for its adaptation to dry environments. Here, we investigated Pro metabolism in different tissues of P. sepium seedlings in the course of drought stress and recovery. We found that leaf Pro metabolism response during post-drought recovery was dependant on drought severity. Pro biosynthesis was down-regulated during recovery from -0.4 MPa but increased continually and notably during recovery from -1.0 MPa. Significant correlation between Pro concentration and Δ1-pyrroline-5-carboxylate synthetase activity indicates that Glutamate pathway is the predominant synthesis route during both drought and re-watering periods. Ornithine δ-aminotransferase activity was up-regulated significantly only during recovery from -1.0 MPa, suggesting positive contribution of ornithine pathway to improving plant recovery capacity from severe drought. In addition to up-regulation of biosynthesis, Pro transport from stems and roots also contributed to high Pro accumulation in leaves and new buds during recovery from -1.0 MPa, as indicated by the combined analysis of Pro concentration and its biosynthesis in stems, roots and new buds. Except its known roles as energy, carbon and nitrogen sources for plant rapid recovery, significant positive correlation between Pro concentration and total antioxidant activity indicates that Pro accumulation can also promote plant damage repair ability by up-regulating antioxidant activity during recovery from severe drought stress.